2020
DOI: 10.1101/2020.09.14.20194589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved estimation of time-varying reproduction numbers at low case incidence and between epidemic waves

Abstract: We construct a recursive Bayesian smoother, termed EpiFilter, for estimating the effective reproduction number, R, from the incidence of an infectious disease in real time and retrospectively. Our approach borrows from Kalman filtering theory, is quick and easy to compute, generalisable, deterministic and unlike many current methods, requires no change-point or window size assumptions. We model R as a flexible, hidden Markov state process and exactly solve forward-backward algorithms, to derive R estimates tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 52 publications
(239 reference statements)
0
28
0
Order By: Relevance
“…Panel (d) plots these R s profiles (top) and the serial interval distributions for each disease (bottom). Generally, we find that t µ is a good approximation to , with some error naturally emerging from the difficulty of estimating R s in conditions where data are necessarily scarce [33]. Our prior distribution over R τ ( j ) is Gam(1, 5), which is both uninformative and has a large mean of 5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Panel (d) plots these R s profiles (top) and the serial interval distributions for each disease (bottom). Generally, we find that t µ is a good approximation to , with some error naturally emerging from the difficulty of estimating R s in conditions where data are necessarily scarce [33]. Our prior distribution over R τ ( j ) is Gam(1, 5), which is both uninformative and has a large mean of 5.…”
Section: Resultsmentioning
confidence: 99%
“…We found that our method generated sensible and reasonably accurate estimates, given the fundamental difficulties of inferring R s at low incidence. Integrating our method with newly developing approaches that improve on R s estimates in these low data conditions [33], should further enhance performance and forms part of our future work. we have ∆t * 95 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vertical lines provide key policy change-times and alert levels in response to these caseloads. The bottom panel presents effective reproduction number ( R ) estimates from EpiFilter 4 (red with 95% confidence bands – these rigorously extract more information from incidence curves than several standard approaches 3 ) and corresponding probabilities (in %) of epidemic elimination ( Z ) – defined as the probability of no future local cases (blue). Both analytics account for the difference between local and imported cases.…”
Section: Main Textmentioning
confidence: 99%